Knowledge Discovery in Databases : PKDD 2006 : 10th European Conference on Principle and Practice of Knowledge Discovery in Databases, Berlin, Germany, September 18-22, 2006 : proceedings - PKDD; Fürnkranz, Johannes; Scheffer, Tobias; Spiliopoulou, Myra (Lecture notes in computer science. Lecture notes in artificial intelligence, 2006)
This book constitutes the refereed proceedings of the 10th European Conference on Principles and Practice of Knowledge Discovery in Databases, PKDD 2006, held in Berlin, Germany in September 2006, jointly with ECML 2006. The 36 revised full papers and 26 revised short papers presented together with abstracts of 5 invited talks were carefully reviewed and selected from 564 papers submitted to both, ECML and PKDD. The papers present a wealth of new results in knowledge discovery in databases and address all current issues in the area.